2016
DOI: 10.1039/c5sc02477c
|View full text |Cite
|
Sign up to set email alerts
|

A flexible iron(ii) complex in which zero-field splitting is resistant to structural variation

Abstract: The zero-field splitting parameters D and E in the iron(ii) complex [Fe(C3S5)2]2– are shown to be remarkably resistant to a twist of the inter-ligand dihedral angle (θd) from 90 to 70°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 66 publications
(30 reference statements)
0
23
0
Order By: Relevance
“…Although no ab initio analysis has been carried out in this work, the positive D in complex 64 may be attributed to the different orbital splitting, and also it is four‐coordinate rather than three‐coordinate as in complex 63 . Four‐coordinate Fe II SIMs have been thoroughly investigated by us and others to probe the origin of magnetic anisotropy [53, 63] . It was found that both positive and negative D values can be obtained in four‐coordination Fe II systems depending on the dihedral or interplanar angle.…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 99%
“…Although no ab initio analysis has been carried out in this work, the positive D in complex 64 may be attributed to the different orbital splitting, and also it is four‐coordinate rather than three‐coordinate as in complex 63 . Four‐coordinate Fe II SIMs have been thoroughly investigated by us and others to probe the origin of magnetic anisotropy [53, 63] . It was found that both positive and negative D values can be obtained in four‐coordination Fe II systems depending on the dihedral or interplanar angle.…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 99%
“…Tailoring the size and sign of D therefore represents a promising strategy to design molecules with a large U. 33 Single-ion magnets (SIMs) containing only one metal center are of particular interest due to the possibility of predicting anisotropy based on ligand field theory. 34,35 However, most transition-metal SIMs are still discovered serendipitously, at least in part both because D relies on subtle geometric effects and accurately predicting a priori the geometry or even stoichiometry of heteroleptic complexes formed from a mixture of ligands remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…While there is ample literature concerning maximizing D , and thus the spin reversal barrier ( U = DS 2 ), considerably fewer reports are devoted to understanding the rational tuning of E through ligand field variations. 9 , 10 A large body of literature in particular exists on magneto-structural correlations in systems with large, negative D values. Yet, in such systems it is very difficult to probe E spectroscopically or magnetically.…”
Section: Introductionmentioning
confidence: 99%